2011
DOI: 10.1099/jmm.0.030536-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropanoids inhibit protofilament formation of Escherichia coli cell division protein FtsZ

Abstract: The earliest step in cell division in bacteria is the assembly of FtsZ, an essential cell division protein, into a ring at the division site. FtsZ has GTPase activity and can assemble in vitro to form protein filaments. The present work involved the study of eight phenylpropanoids (cinnamic, p-coumaric, caffeic, chlorogenic, ferulic, 3,4-dimethoxycinnamic and 2,4,5-trimethoxycinnamic acids and eugenol) as inhibitors of Escherichia coli FtsZ. Phenylpropanoids make up the majority of our diet and act as antibact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Cinnamaldehyde was suggested to inhibit cytokinesis as a mode of action on B. cereus because cells could not separate although septa were present after division (Kwon et al, 2003). It has been established that cinnamaldehyde binds to the FtsZ protein, inhibiting its GTP dependent polymerization and thereby preventing cell division (Domadia et al, 2007; Hemaiswarya et al, 2011). The FtsZ protein is an attractive target for antimicrobial therapies as it is evolutionary distant from eukaryotic tubulin, and the predicted interaction of H2 and H3 of cinnamaldehyde with G295 and V208 of FtsZ, respectively, is conserved among FtsZ proteins from several species (Domadia et al, 2007; Hemaiswarya et al, 2011).…”
Section: Essential Oil Constituent Classes: Their Antimicrobial Activmentioning
confidence: 99%
See 1 more Smart Citation
“…Cinnamaldehyde was suggested to inhibit cytokinesis as a mode of action on B. cereus because cells could not separate although septa were present after division (Kwon et al, 2003). It has been established that cinnamaldehyde binds to the FtsZ protein, inhibiting its GTP dependent polymerization and thereby preventing cell division (Domadia et al, 2007; Hemaiswarya et al, 2011). The FtsZ protein is an attractive target for antimicrobial therapies as it is evolutionary distant from eukaryotic tubulin, and the predicted interaction of H2 and H3 of cinnamaldehyde with G295 and V208 of FtsZ, respectively, is conserved among FtsZ proteins from several species (Domadia et al, 2007; Hemaiswarya et al, 2011).…”
Section: Essential Oil Constituent Classes: Their Antimicrobial Activmentioning
confidence: 99%
“…It has been established that cinnamaldehyde binds to the FtsZ protein, inhibiting its GTP dependent polymerization and thereby preventing cell division (Domadia et al, 2007; Hemaiswarya et al, 2011). The FtsZ protein is an attractive target for antimicrobial therapies as it is evolutionary distant from eukaryotic tubulin, and the predicted interaction of H2 and H3 of cinnamaldehyde with G295 and V208 of FtsZ, respectively, is conserved among FtsZ proteins from several species (Domadia et al, 2007; Hemaiswarya et al, 2011). Other enzymes, e.g., the histidine decarboxylase, is also inhibited by cinnamaldehyde (Wendakoon and Morihiko, 1995).…”
Section: Essential Oil Constituent Classes: Their Antimicrobial Activmentioning
confidence: 99%
“…Chlorogenic acid, another phenolic compound, is an important biosynthetic intermediate, for example in lignin biosynthesis. Studies showed that chlorogenic acid displayed antibacterial and antifungal activity against certain microorganisms (Sung and Lee 2010;Hemaiswarya et al 2011;Atanasova-Penichon et al 2012). In ginseng callus cultures, accumulation of phenolic compounds was increased 3-fold within 12 h after 1 % chitosan treatment.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…According to Kwon et al [100] cinnamaldehyde inhibited cytokinesis in Bacillus cereus by inhibiting the septum formation. It has been established that cinnamaldehyde binds to the FtsZ protein, inhibiting its GTPdependent polymerization and thereby preventing cell division [101]. Besides, enzymes like histidine decarboxylase are also inhibited by cinnamaldehyde [97].…”
Section: Mechanism Of Actionmentioning
confidence: 99%